Improvement and Force Analysis of Flying Shear Gearbox with Single Flywheel for Hot- rolled Plate - Liu Qingfeng; Chen Tao (Jixie chuandong)
The principle of crank and connecting rod mechanism for the flying shear gear box is analyzed,and a general model of maximum shear torque is deduced for this mechanism. The power flow of the transmission unit is also distributed according to the work- energy transformation principle in a full shear cycle. On this basis,the FEM force calculation and improvement of the flying shear gear box are carried out. The case study indicates that shear gearbox with single flywheel has the asymmetric characteristic,and the improved gearbox has better rigidity distribution and reliability.